The Irrationality of GOF Avian Influenza Virus Research - Wain-Hobson, Simon (Frontiers in Public Health, 2014)
The last two and a half years have witnessed a curious debate in virology characterized by a remarkable lack of discussion. It goes by the misleading epithet “gain of function” (GOF) influenza virus research, or simply GOF. As will be seen, there is nothing good to be gained. The controversial experiments confer aerosol transmission on avian influenza virus strains that can infect humans, but which are not naturally transmitted between humans. Some of the newer strains are clearly highly pathogenic for man. It will be shown here that the benefits of the work are erroneous and overstated while the risk of an accident is finite, if small. The consequence of any accident would be anywhere from a handful of infections to a catastrophic pandemic. There has been a single open international meeting in two and a half years, which is surprising given that openness and discussion are essential to good science. Despite US and EU government funding no risk-benefit analysis has been published, which again is surprising. This research can be duplicated readily in many labs and requires little high tech. It falls under the definition of DURC without the slightest shadow of a doubt and constitutes the most important challenge facing contemporary